Cучасний погляд на ідею використання гамма-аміномасляної кислоти та її метаболіта для відновлення моторної функції - Родинський, О. Г.; Демченко, Т. В.; Мозгунов, О. В.; Писаревська, К. В.; Родинский, А. Г.; Мозгунов, A. В.; Писаревская, К. В.; Rodinskij, А. G.; Dемchenko, Т. V.; Mozgunov, А. V.; Pysarevska, К. V. (Запорізький державний медичний університет, 2015)
З метою вивчення можливостей використання гамма-аміномасляної кислоти та її метаболітів як медичних препаратів за умов пошкодження периферичної нервової системи здійснили огляд спеціалізованої літератури. Розглянули сучасні проблеми відновлення функцій денервованих м’язів і широкий спектр ефектів ГАМК та її метаболітів, що могли б бути корисними в умовах травми. Як природна ендогенна сполука з елементами ноотропної, антигіпоксично-антиоксидантної, органопротективної, анаболічної та антиноцицептивної активності, ГАМК відповідає всім критеріям, поєднання котрих могло б сприяти процесам посттравматичного відновлення. Здатність ГАМК підвищувати концентрацію Са2+ після травми може впливати на експресію генів, напрям руху конуса росту, а, можливо, й знижувати клітинну загибель від субоптимального цитозольного Са2+. Це свідчить про те, що ГАМК має селективність дії щодо пошкодженої структури та може cтати доволі перспективним агентом для відновлювальної терапії. С целью изучения возможностей использования гамма-аминомасляной кислоты и её метаболитов в качестве медицинских препаратов в условиях повреждения периферической нервной системы провели обзор специализированной литературы. Рассмотрели современные проблемы восстановления функций денервированных мышц и широкий спектр эффектов ГАМК и её метаболитов, которые могли бы быть полезными в условиях травмы. Как естественное эндогенное соединение с элементами ноотропной, антигипоксично-антиоксидантной, органопротективной, анаболической и антиноцицептивной активности, ГАМК соответствует тем критериям, сочетание которых могло бы способствовать процессам посттравматического восстановления. Способность ГАМК повышать концентрацию Са2+ после травмы может влиять на экспрессию генов, направление движения конуса роста, а, возможно, и снижать клеточную гибель от субоптимального цитозольного Са 2+. Это свидетельствует о том, что ГАМК имеет селективность действия по отношению к повреждённой структуре и может быть довольно перспективным агентом для восстановительной терапии. Aim. The literature review is devoted to the idea of using gamma-aminobutyric acid and its metabolites as medicines in conditions of peripheral nervous system injury. We examined the modern problems of denervated muscles restoration and a wide range of GABA effects which could be useful in conditions of injury. GABA and its metabolites have elements of nootropic, antihypoxic, organoprotective and anabolic activity. It is obvious that traumas of peripheral nerves lead to degeneration of injured fi bers and signifi cant disorders of metabolism at a number of regulatory levels. Regeneration of the nerve and the rate of recovery of muscle activity depend significantly on the level of resistivity of the injured nerve tissue and on possibilities for supply of this tissue by additional energetic reserves. Under the above-mentioned conditions, disorders are determined, to a signifi cant extent, by the development of hypoxia. This is why elucidation of the phenomenology and mechanisms of action of GABA and its metabolites (agent are having, as was mentioned above, protective and antihypoxic properties) on the nerve/muscle apparatus and its links under conditions of traumatization of a large nerve is urgent. GABA and its metabolites have an antinociceptive activity which helps not only in inhibition of central and spinal neurons, but also helps to decrease pain sensitivity of patient after traumatic neuropathy to forming of motivation to recovery rehabilitation. Besides above mentioned, the ability of GABA to increase concentration of Ca2+ after injury was discussed. This ability may affect the expression of genes, the direction of the growth cone, and, perhaps, reduce cell death. Conclusion. This indicates that the GABA has a selectivity of action to the damaged structure and can be prospective agent for regenerative therapy.
Современный взгляд на идею использования гамма-аминомасляной кислоты и её метаболита для восстановления моторной функции
The modern view of the idea of gamma-aminobutyric acid and its metabolite use to restore the motor function
Keywords: гамма-аміномасляна кислота (ГАМК); гамма-гідроксимасляна кислота (ГГОМК); периферичні; нейропатії; відновлення; ноотропи; травми нервової системи; гамма-аминомасляная кислота (ГАМК); гамма-гидроксимасляная кислота (ГГОМК); периферические нейропатии; восстановление; ноотропы; травмы нервной системы; gamma-Aminobutyric Acid (GABA); gamma-Hydroxybutyric Acid (GHBA); Peripheral Neuropathies; Recovery of Function; Nootropic Agents; Nervous System Injuries